Peran Kepemimpinan dalam Keberhasilan Pengembangan Paguyuban Petani Al Barokah di Desa Ketapang Kecamatan Susukan Kabupaten Semarang Jawa Tengah - Dias Ayu Ambarsari; Lasmono Tri Sunaryanto (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2022)
Leadership is a behavior in the process of social control that can affect the lives of other people and power in influencing the behavior of others to direct the achievement of specific goals (Mustapa & Maryadi, 2017). The purpose of this study was to analyze the role of leadership and leadership style in the development of the Al Barokah Farmers Association. The study was conducted from February to July 2022 in the Al Barokah Farmers Association, located in Ketapang Village, Susukan District, Semarang Regency, Central Java. The research showed using qualitative methods with descriptive data. The unit of analysis in this study is the executive board of the Al Barokah Farmers Association. Meanwhile, the team of observation in this study includes the leadership role of the chief executive of the Al Barokah Farmers Association based on Henry Mintzberg's theory and leadership style based on the Path-Goal leadership theory. Data collection techniques by observation, documentation, and interviews. Data analysis techniques include 1) data reduction, 2) data presentation, and 3) drawing conclusions and verification. The results of the study show that the leadership role carried out by the chief executive is seen from attending a meeting or formal event as a representative of the community, the direction from the chief executive to make programs based on the needs of members, playing a role in determining even dominant in recommending appropriate relationships with Al Barokah's vision and mission, holding an RAT (Annual Membership Meeting) led by the executive chairman, together with the association to resolve hoax issues that occurred, from an agreement of the executive chairman as a representative of the association with the director of BNI and the Ministry of Cooperatives regarding the cooperation of KUR with BNI and the launch digital cooperative in Al Barokah, the establishment of an agreement on the buying and selling process between the chief executive and the buyer from the Netherlands, the control of organic farming activities of farmer members through the ICS (Internal Control System) under the auspices of the chief executive, from the direction of the chief executive to allocate human resources for the children of farmers to assist in the digitization of agriculture in Al Barokah, and how to select the assistance that enters the community by holding a meeting chaired by the chief executive. Meanwhile, the leadership style that occurs in the Al Barokah Farmers Association is supportive and participatory.